P572 Therapy optimisation and intravenous ferric carboxymaltose in active or inactive IBD with iron deficiency: it's time to make iron deficiency part of tight monitoring to reach T2T? – preliminary results of a prospective study. (21st January 2022) - Molnár, T; Resál, T; Bacsur, P; Rutka, M; Szántó, K; Bálint, A; Milassin, Á; Fábián, A; Bor, R; Szepes, Z; Farkas, K
Abstract: Background: Iron deficiency (ID) is often a neglected condition in inflammatory bowel disease (IBD), even though it is one of the most common extraintestinal manifestation. Our questions were the follows: If iron deficiency is part of the T2T management as CRP or fecal calprotectin and requires optimisation of the current therapy, how does this affect the medium-term outcome of the disease and the effectiveness of IV iron replacement? If the disease is active, does optimisation of therapy is sufficient to manage iron deficiency or iv. iron supplementation is also necessary? Methods: Patients with ID defined by the ECCO guideline (Figure 1.) were randomly included in our prospective one-center, four arms study. Patients were divided into an active (A) and a remission (R) group. Activity was defined by CRP ≥10 mg/l or clinical activity scores CDAI ≥150, pMayo ≥3. Therapy optimisation was performed in the active group, further randomisation was performed into two subgroups: therapy modification alone (A1) or modification with iv. ferric-carboxymaltose (A2). All patients received iron supplementation in the remission group with (R2 – iron T2T group) or without therapy optimisation (R2). Every two months laboratory parameters and clinical activities were assessed until 6 months. Results: 65 patients were included (CD 83.4%). Average follow-up was 3.9 months. Number of patients per group: A1:17, A2:23, R1:16, R2:9. Based on our results, iv. iron supplementation with modification in treatment was more efficient, than therapy optimisation alone, as the difference in increase in haemoglobin (p<0.001), haematocrit (p<0.001) and ferritin (p<0.05) was significant after 2 and 4 months the enrollment. In the remission group iv. iron supplementation with therapy optimisation was more effective, than iv. iron alone, based on transferrin saturation (p<0.05), serum iron (p<0.05) and CRP (p<0.05) during the 2 months period. After that period, no further significant difference was measured. Iv. iron seems to be equally effective both in the active and in the remission group, as no significant difference was measured during the 6-month period. No adverse event was observed. Conclusion: Our results suggest, that therapy optimisation in addition to iron replacement is more effective in patients with remission and therefore biomarkers of IDA should be involved in the thight monitoring algorhytm to react T2T. However, therapy optimisation has to be associated with iv iron replacement in IBD with IDA and activity without the risk of worsening disease activity. Based on our results, ferric-carboximaltose is an effective and safe therapeutic method in the treatment of IDA associated with active or inactive IBD.